Respuesta :

Answer:

No solution or B

Step-by-step explanation:

Multiply eq1 by 3.

3y=18x+6

3y-18x=12

Regroup:

18x-3y=-6

-18x+3y=12

Add:

0=6???

Impossible

So no solution.

Hope this helps plz mark brainliest :D

Answer:

No solution

Step-by-step explanation:

First we need to solve the equations.

I'll use the combining method

To do the combining method you need to get one of the variables in the first equation to be the negative correspondent to the same variable in the second equation.

(Ex:

If there was 2x in the first equation we would want there to be -2x in the second so they cancel out.)

y=6x+2

subtract 6x from each side to get the variables to line up

y-6x=2

3y-18x=12

To get -6x to equal 18x, we will multiply everything in the first equation by -3

-3y+18x=-6

3y-18x=12

Now combine the two terms

-3y and 3y cancel out

18x and -18x cancel out

-6+12=6

We are left with 0=6.

0 does not equal 6 so there is no solution.

ACCESS MORE